Edukasi Penjaminan Perlindungan Sosial Ekonomi Meninjau Kaum Gen Z Pada Komunitas Young Helper Melalui Program BPJS Ketenagakerjaan - Fadhil Pradwira Ilham; Riza Rivaldiansyah Daza; Raden Achmad Rafi Adyatma; Anggi Alvionita; Ardana Pradipta Andhika Putra; Rama Gala Dewa; Muhammad Rafino Zalia; Muhammad Arief Prawira Nugraha; Muhammad Ariq Ramadhan; Abdul Kalam Arif; Lutfi Hardiyanto (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
The BPJS Employment program is an important aspect in providing socio-economic protection for Indonesian people, especially Generation Z (Gen Z), who are starting to enter the world of work. This service aims to increase understanding of the BPJS Employment program through education carried out in the Young Helper community, a volunteer organization that is committed to creating positive change in society and is part of Gen Z. This service also aims to increase Gen Z's participation in the BPJS Employment Program which provides socio-economic security. The method used in this service is an educational method through the presentation of interactive material with data sources from literature studies, questionnaires, interviews and field observations. Our service contains educational teaching on the BPJS Employment Program such as requirements, technical implementation, types of programs and how to register. The education we carry out produces pamphlets, powerpoints, educational videos and posters, each of which presents important information from the BPJS Employment Program. The results of our service show that there is an increase in participants' understanding and participatory desire to be registered in the BPJS Employment Program.